2017
DOI: 10.1044/2017_jslhr-l-15-0446
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Working Memory for Words and Nonwords in Cerebral Cortex

Abstract: Purpose: The primary purpose of this study was to identify the brain bases of phonological working memory (the shortterm maintenance of speech sounds) using behavioral tasks analogous to clinically sensitive assessments of nonword repetition. The secondary purpose of the study was to identify how individual differences in brain activation were related to participants' nonword repetition abilities. Method: We used functional magnetic resonance imaging to measure neurophysiological response during a nonword disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 121 publications
9
29
0
Order By: Relevance
“…Regardless of the polarity of the effect, the current study shows that the left pIFG exhibits a functional specialization for phonological processing in word production. This is in line with previous neuroimaging research arguing for an involvement of this area in syllabification (de Zubicaray & Piai, ; Indefrey, ), but also underlines its role in phonological working memory (Perrachione, Ghosh, Ostrovskaya, Gabrieli, & Kovelman, ; Zurowski et al, ). Critically, by employing a rhyme production task, our study extends previous studies using phonemic fluency tasks, in which speakers are asked to name as many words as possible starting with a given letter.…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of the polarity of the effect, the current study shows that the left pIFG exhibits a functional specialization for phonological processing in word production. This is in line with previous neuroimaging research arguing for an involvement of this area in syllabification (de Zubicaray & Piai, ; Indefrey, ), but also underlines its role in phonological working memory (Perrachione, Ghosh, Ostrovskaya, Gabrieli, & Kovelman, ; Zurowski et al, ). Critically, by employing a rhyme production task, our study extends previous studies using phonemic fluency tasks, in which speakers are asked to name as many words as possible starting with a given letter.…”
Section: Discussionsupporting
confidence: 91%
“…That is, as stimulus-specific details of speech are internally represented in memory (Lim et al, 2015(Lim et al, , 2018, speech spoken by one consistent talker might be more efficiently represented in working memory than speech spoken by different talkers, even if the speech carries the same linguistic message (see below for a discussion of potential differences in memory representations). This possibility is consistent with an emerging neurobiological model of speech working memory, which posits that maintenance of speech information in memory relies on the very same brain networks involved in speech perception and production (Hickok, 2009;Jacquemot & Scott, 2006;Perrachione, Ghosh, Ostrovskaya, Gabrieli, & Kovelman, 2017). Thus, the speech working memory store might remain susceptible to variability-related interference such as that observed during immediate recognition.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed that non-alphabetic tasks predict later reading performance (Lervåg and Hulme, 2009;Parrila et al, 2004) without being biased by reading experience (Rakhlin et al, 2013) or early differences in reading ability as for alphabetic items (Bowey and Muller, 2005). Deficits in pWM have been consistently documented in language-based learning disabilities and usually persist throughout life, suggesting a deficit rather than a developmental delay model (Perrachione et al, 2017;Swanson et al, 2009). Phonological WM is thought to support a wide range of linguistic behaviors, including novel word learning and vocabulary development, maintenance of information during sentence and discourse processing, and the acquisition of reading skill.…”
Section: Discussionmentioning
confidence: 99%